Potensi Fraksi Etil Asetat Ekstrak Daun Gambir (Uncaria gambir Roxb.) sebagai Antihiperlipidemia - Yunarto, Nanang; Elya, Berna; Konadi, Laurentia (Jurnal Kefarmasian Indonesia, 2015)
Hyperlipidemia is the main risk factor for atherosclerosis and coronary heart disease. Ethyl acetate fraction of gambier leaves extract (Uncaria gambir Roxb.) contains catechin secondary metabolites which have potency to be used as antihyperlipidemic. This study aimed to examine the antihyperlipidemic effect of ethyl acetate fraction of gambier leaves extract in vivo. Thirty six males of Sprague Dawley strain, 2,5 months old, were randomly divided into six groups: normal group, negative group (distilled water), positive group (simvastatin 2 mg/200 g bw), dose I (5 mg/200 g bw fraction), II (10 mg/200 g bw fraction) and III (20 mg/200 g bw fraction) groups. Rats were induced with high cholesterol and saturated fat feeds for 28 days, except in the normal group. Furthermore, rats were given the treatment for 28 days. The results showed when compared than negative control, dose III reduced of total cholesterol, triglycerides, LDL levels and increased HDL level (p